2014
DOI: 10.1038/ki.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

No significant effect of angiotensin II receptor blockade on intermediate cardiovascular end points in hemodialysis patients

Abstract: Agents blocking the renin-angiotensin-aldosterone system are frequently used in patients with end-stage renal disease, but whether they exert beneficial cardiovascular effects is unclear. Here the long-term effects of the angiotensin II receptor blocker, irbesartan, were studied in hemodialysis patients in a double-blind randomized placebo-controlled 1-year intervention trial using a predefined systolic blood pressure target of 140 mm Hg (SAFIR study). Each group of 41 patients did not differ in terms of age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 64 publications
5
46
0
Order By: Relevance
“…Preservation of renal function could improve dialysis care and previous studies in PD patients have suggested a significant effect of renin‐angiotensin‐aldosterone system blockade . However, in the SAFIR study no significant associations were shown between the angiotensin II receptor blocker irbesartan and preservation of renal function or intermediate cardiovascular endpoints …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Preservation of renal function could improve dialysis care and previous studies in PD patients have suggested a significant effect of renin‐angiotensin‐aldosterone system blockade . However, in the SAFIR study no significant associations were shown between the angiotensin II receptor blocker irbesartan and preservation of renal function or intermediate cardiovascular endpoints …”
Section: Discussionmentioning
confidence: 85%
“…See modified CONSORT flow chart in Figure . For the original CONSORT flow chart see previous publications . There were no significant differences between patients who completed all three questionnaires and patients who dropped out in terms of HRQOL at baseline.…”
Section: Resultsmentioning
confidence: 94%
“…The absence of benefit with RAS‐blockers is further supported by the Saving Residual Renal Function among Hemodialysis Patients Receiving Irbesartan Study (SARIF) . This trial showed that among 82 incident hemodialysis patients, 12‐month‐long therapy with the ARB irbesartan was not superior to placebo in causing regression of target‐organ damage, as assessed by measuring Left Ventricular Mass Index (LVMI) and aortic pulse wave velocity (PWV) …”
Section: Pharmacological Management Of Hypertensionmentioning
confidence: 99%
“…Choice of the appropriate antihypertensive regimen among those on hemodialysis should not rely on extrapolation of evidence derived from the general population or those with earlier stages of chronic kidney disease . To wit, trials that evaluated the efficacy of ACEIs/ARBs suggest that their use as first‐line antihypertensive therapy in hemodialysis patients is not supported by strong evidence of a cardiovascular benefit . By contrast, the BP‐lowering efficacy of atenolol in the HDPAL and its premature termination due to excess risk for serious cardiovascular adverse events in lisinopril‐treated participants support the use of β‐blockers as first therapeutic choice .…”
Section: Pharmacological Management Of Hypertensionmentioning
confidence: 99%
“…Their title was very impressive as previous studies proved the effects of an angiotensin receptor antagonist on hard end points in dialysis patients including our study. 2 Originally, the purpose of central aortic blood pressure measurement was to detect the minute changes in vessels, which would not change the brachial blood pressure. Therefore, measurement of central aortic blood pressure might not be suitable for dialysis patients who show a high value because of aging and advanced arterial calcification.…”
mentioning
confidence: 99%